Пристрій обробки лідарного сигналу - Петров, О. В.; Зарудний, О. А. (ХНУРЕ, 2018)
The work is devoted to the development of a lidar signal processing de-vice. The main problem in the development of the lidar receiver is the detection of very weak and rapidly changing optical radiation fluxes, which are laser radi-ation scattered in the atmosphere, collected and directed to the photodetector by an optical telescope. Based on the analysis of existing lidar systems, a device for processing the lidar signal on the basis of a computer is proposed, which is in-cluded in the circuit and performs the functions of control, adaptation, testing, and processing of the obtained data.
Keywords: лідар; фотоелектронний помножувачь